Actualization Pancasila Values through the Tapai Festival Tradition in Batu Bara Regency - Safitri, Ira; Sundawa, Dadang; Suwardani, Ni Kadek (Pancasila: Jurnal Keindonesiaan, 2026)
Pancasila is the foundation of the state and a guideline for the Indonesian people. Its existence serves as a guide for behavior and activities in daily life. Therefore, every citizen must uphold the values of Pancasila in their social, national, and state life without exception. However, in reality the values of Pancasila have faded with the times due to the many problems that occur in society. Some of these problems include intolerance, indifference, moral decadence among the younger generation, a decline in the spirit of mutual cooperation, conflicts between communities, the fading of deliberative consensus, and social and economic inequality. When the values of Pancasila are not actualized in life, these problems will continue to occur and may even have a worse impact than they do today. This study aims to examine how the values of Pancasila are actualized through the tradition of the Tapai Festival in Batu Bara Regency. The research method used is a qualitative research method with a phenomenological approach. The data collected are primary and secondary data. Primary data are in the form of observations and interviews. Meanwhile, secondary data are in the form of reference books, journal articles, the internet, and others. The data analysis used is the Miles and Huberman approach. The results of the study show that the implementation of the Tapai Festival tradition in Batu Bara Regency has actualized the values of Divinity, Humanity, Unity, Democracy, and Social Justice as reflected concretely in the daily lives of the people of Batu Bara.